2017
DOI: 10.1177/0033354916689610
|View full text |Cite
|
Sign up to set email alerts
|

Engagement in the Hepatitis C Care Cascade Among Homeless Veterans, 2015

Abstract: The Veterans Health Administration (VHA) is the largest provider of hepatitis C virus (HCV) care nationally and provides health care to >200 000 homeless veterans each year. We used the VHA's Corporate Data Warehouse and HCV Clinical Case Registry to evaluate engagement in the HCV care cascade among homeless and nonhomeless veterans in VHA care in 2015. We estimated that, among 242 740 homeless veterans in care and 5 424 712 nonhomeless veterans in care, 144 964 (13.4%) and 188 156 (3.5%), respectively, had ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…( 4,6‐9 ) Despite the high prevalence of HCV among homeless persons, a significant proportion still remains undiagnosed and consequently untreated. ( 10 )…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…( 4,6‐9 ) Despite the high prevalence of HCV among homeless persons, a significant proportion still remains undiagnosed and consequently untreated. ( 10 )…”
mentioning
confidence: 99%
“…( 11 ) However, despite the potential benefit of this testing approach and efficacy of DAAs, suboptimal uptake of HCV treatment persists among homeless adults. ( 10,12,13 )…”
mentioning
confidence: 99%
“…For example, among chronically infected formerly incarcerated individuals in one study, 57% were referred to an HCV provider, but only 36% were medically evaluated, and only 10% initiated treatment . A study among homeless veterans found that those who were homeless were more likely to be identified and medically evaluated by an HCV provider but less likely to initiate HCV treatment compared to veterans who were not homeless . Better outcomes were found among opioid users undergoing substance abuse treatment, where 71% of persons with chronic HCV infection initiated treatment .…”
mentioning
confidence: 99%
“…(12) A study among homeless veterans found that those who were homeless were more likely to be identified and medically evaluated by an HCV provider but less likely to initiate HCV treatment compared to veterans who were not homeless. (13) Better outcomes were found among opioid users undergoing substance abuse treatment, where 71% of persons with chronic HCV infection initiated treatment. (14) In addition, a study in a Baltimore sexually transmitted infections clinic found high linkage to care rates among persons who were referred to off-site specialists, with the assistance of patient navigation.…”
mentioning
confidence: 99%
“…Among the 250,000 homeless veterans (HVs) that receive care in the Veterans Health Administration (VA), 13.4% have chronic hepatitis C virus (HCV) infection . As of 2015, only 22.9% of HVs receive antiviral therapy, considerably lower than the 31% of their nonhomeless counterparts that undergo HCV treatment .…”
mentioning
confidence: 99%